Geochemical barriers of manganese distribution in edaphotopes of Dnieper Prysamarye - N. N. Tsvetkova; Y. O. Tagunova (Vìsnik Dnìpropetrovsʹkogo Unìversitetu: Serìâ Bìologìâ, Ekologìâ, 2015)
Microelement composition is an important condition of edaphotopes as the major, summarizing parts of any biogeocenosis. Microelements in ultra-microquantity are necessary for vital functions of all organisms, but their anthropogenic accumulation and transformation in soil environment represents a real threat for living organisms’ health and stability of the biosphere as a whole. Geochemical barriers are local zones where the conditions of elemental migration are significantly different, resulting in accumulation of some chemical elements. The relevance of geochemical barriers’ study consists in the prospective possibility of artificial limitation of the migration of polluting elements in the environment. The aim of this research is to determine the role of geochemical barriers in distribution and migration of manganese in edaphotopes of Dnieper Prysamarye. Content of manganese in soils, regularity of its distribution and relationship between a number of physical and chemical properties of soils were considered in the course of investigation. Besides, this paper summarizes the main features and regularities of the different geochemical barriers’ formation. Manganese content in soils was analyzed by atomic absorption spectrophotometry. The objects of the research are edaphotopes of the biogeocenoses of Dnieper Prisamarye situated in steppe zone of Ukraine, subzone of forb-fescue-stipa steppe. According to our data, the average concentrations of manganese in the horizons of 0–50 cm of ordinary chernozem, alkaline-saline meadow-forest soil, floodplain meadow-forest and sod upland soils are 495 ± 24, 610 ± 223, 810 ± 220, 51 ± 11 mg/kg of ovendry weight soil, respectively. Furthermore, the authors investigated the correlation between the content of manganese and absorption capacity, humus content, composition of exchange cations, pH and dry residue of soils under study. The results obtained demonstrate that specific soil horizons can be regarded as geochemical barriers in the dissemination of manganese. Furthermore, it was found that the greatest impact on the distribution of manganese was exerted by pH (and, consequently, the carbonate content) and amount of humus in soil. This fact allows to consider pH and humus content as the geochemical and biological barriers for migration of manganese, respectively. It has been also concluded that establishing of the relation between physical and chemical properties of soil and its microelement composition could give an opportunity to regulate the content of microelements in edaphotopes of different biogeocenoses and to improve their living conditions thereby.